Intervention with women Victims of gender Violence:Educate and inform to prevent (2015)
Any person, who has been the victim of a crime, is dismayed, frustrated, and in many circumstances without knowing what to do, especially if these crimes are committed by the couple or the former couple, because of the link that connect each other. This is why professionals in the field of the intervention with victims of gender-based violence in relationships, or in another situation, it is important that they, professionals, are able to develop a special awareness and empathy when they have to intervene the persons with these circumstances because of the condition of vulnerability in which they are.